2020
DOI: 10.1136/bjophthalmol-2020-315948
|View full text |Cite
|
Sign up to set email alerts
|

Impact of contact versus non-contact wide-angle viewing systems on outcomes of primary retinal detachment repair (PRO study report number 5)

Abstract: Background/aimsVitrectomy to repair retinal detachment is often performed with either non-contact wide-angle viewing systems or wide-angle contact viewing systems. The purpose of this study is to assess whether the viewing system used is associated with any differences in surgical outcomes of vitrectomy for primary non-complex retinal detachment repair.MethodsThis is a multicenter, interventional, retrospective, comparative study. Eyes that underwent non-complex primary retinal detachment repair by either pars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The three surgeons with less recurrences use non-contact viewing systems for vitrectomy, compared to the contact viewing systems used by the rest of the surgeons. Recently, the PRO study reported no differences in anatomic success between non-contact and contact viewing systems [ 33 ]. Mazinani et al examined the relationship between experience and success rates and observed that primary anatomical success rate became stable after 500 vitreoretinal procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The three surgeons with less recurrences use non-contact viewing systems for vitrectomy, compared to the contact viewing systems used by the rest of the surgeons. Recently, the PRO study reported no differences in anatomic success between non-contact and contact viewing systems [ 33 ]. Mazinani et al examined the relationship between experience and success rates and observed that primary anatomical success rate became stable after 500 vitreoretinal procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This study is in compliance with the Health Insurance Portability and Accountability Act, received approval from all institutional review boards, and adhered to the tenets of the Declaration of Helsinki. We report a subgroup analysis from the PRO Study, which has been previously described in detail (Ryan, Joseph, et al., 2020; Ryan, Ryan, et al., 2020; Tieger et al., 2020; Wang et al., 2019). This study compares pre and intraoperative metrics between the surgeons with the highest SSSR versus those with the lowest SSSR for primary RRD surgery as well as the surgical approaches for the following patients: phakic, pseudophakic, superior RRD, inferior RRD, and RRDs with lattice.…”
Section: Methodsmentioning
confidence: 99%
“…However, when controlling for case complexity, intra-operative 360° laser retinopexy was significantly associated with lower final anatomic success and worse final visual acuity. Following this report, the PRO team focused on outcomes of vitrectomies done with a contact versus a noncontact wide-angle lens during primary RRD repair [10]. In this cohort, there were 363 eyes that underwent surgery with a contact lens system and 1893 eyes in the noncontact viewing system cohort.…”
Section: Introductionmentioning
confidence: 99%